IPTEKS PENGENDALIAN SISTEM PENCATATAN PERSEDIAAN PADA PT BERLIAN KHARISMA PASIFIK - Lambidju, Nona Erlita; Rundengan, Fanda (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
PT. Berlian Kharisma Pasifik is a limited liability company engaged as a distributor of Pertamina lubricants. Therefore this company has inventory which is a major part of supporting the company's operations. Based on research conducted at PT. Berlian Kharisma Pasifik, the conclusion that can be taken is that corporate control must be maximized to minimize the risks that may occur in inventory management. There are a number of points that can help companies control inventory, including inventory storage management by setting appropriate operational standards, conducting inventory operations and checking inventory regularly, and using technology and software to manage inventory. Suggestions for companies to further optimize company inventory control need to pay attention to data collection and inventory recording systems. Companies can use special or manual software with MS. Superior. And the most important is discipline in recording the entry and exit of goods and always records for the stock of items that are damaged or lost, encoded and recorded properly and neatly.Keywords: Inventory Recording System, Inventory Management